Fatty Acid Profile and Chemical Composition of Three Populations of Southern Cattail (Typha domingensis) from South of Iran - Mona Shojaee Barjouee; Massoumeh Farasat; Mehrnoosh Tadayoni (مجله پژوهش‌های علوم و صنایع غذایی ایران)
Lipids are comprised of heterogenous group of chemical compounds, the majority of which have fatty acids as part of their structure. Fatty acids (FAs) are essential for the normal functioning of all organisms. Polyunsaturated fatty acids with multiple double bonds (PUFAs), including omega-3 (n-3) and omega-6 (n-6) are known as beneficial chemicals for human health. Recent attempts to find and identify oils with special advantageous qualities have been prompted by the widespread use of vegetable oils in the food and other industries. Southern cattail (Typha domingensis) is a plant whose practically all parts are edible, particularly its starchy rhizomes, which have a protein composition comparable to corn or rice. In this study, to investigate the nutritional value of this plant, plant samples were collected from three locations in the south of Iran, including Shadegan Wetland, Hoveyzeh (Hoorolazim Wetland), and Hamidabad (Dez River). The oil content and fatty acid profile as well as some chemical compositions such as ash, moisture, fiber, protein, and carbohydrates were evaluated and compared. The oil was extracted using the Soxhlet technique, and the fatty acid composition was determined by GC/MS. The average oil content in aerial (stems and leaves) and underground (rhizomes and roots) organs was 2.62 and 1.52%, respectively. The samples contained 12 fatty acids, three of which were unsaturated and nine were saturated. In roots and rhizomes, the maximum proportion of unsaturated fatty acids including oleic acid (ω-9), linoleic acid (ω-6), alpha- linolenic acid (ω-3) was 65.85±1.51%, whereas in stems and leaves, it was 41.10±0.09%. The amounts of fiber, moisture, ash, protein, and carbohydrates in the samples ranged from 43.34 to 45.93%, 12.57 to 17.84%, 3.64 to 4.25%, 6.20 to 6.40%, and 23.19 to 32.18%, respectively. This plant's high fiber content with the capacity to grow quickly and widely in fresh and saline water make it a viable candidate for inclusion in human diet and animal feed through agricultural breeding initiatives.